Evaluation of Health Care Workers’ Knowledge about Acute Flaccid Paralysis in Najaf City/Iraq - Hala J. Jasim; Naja H. Hassan (مجلة الكوفة الطبية)
Background: Acute Flaccid Paralysis (AFP) is a severe clinical symptom that could have a variety of different causes. Acute flaccid paralysis (AFP) is a clinical symptom characterized by the sudden onset of weakness or paralysis and decreased muscle tone (less periodic muscles of the respiratory tract). It occurs in 0.1–1% of infected cases and is the most frequent clinical manifestation of acute poliovirus infection[1]. Methods: A study of cross-sectional descriptive study was carried out in 18 primary healthcare centers located in 2 districts of Najaf city, using the method of simple random sampling technique.  The research study includes 210 primary healthcare workers. A questionnaire was used to evaluate the acute flaccid paralysis knowledge of healthcare workers.  Data collection from November 1, 2023, to the of February 31, 2024. Results: The study revealed a significant level of moderate knowledge among healthcare workers. Additionally, a statistically significant link was observed between the healthcare workers' levels of education and their knowledge (P < 0.00),    Considering years of experience, the findings indicate that a greater proportion of healthcare workers (34%) with <1-5 years of experience had strong knowledge compared to those with other levels of experience , with a p-value of 0.005. Conclusion: Healthcare workers showed a moderate level of knowledge regarding Acute Flaccid Paralysis information, and the knowledge was strongly related to the healthcare worker's levels of education and years of experience.